Kinerja Pertumbuhan Larva Ikan Depik (Rasbora tawarensis) dengan Tingkat Pemberian Pakan yang Berbeda - Siti Komariyah; Hilwatun Nisa; Iwan Hasri (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Depik fish (Rasbora Tawarensis) is one of the endemic fish of Lake Laut Tawar which has high economic value. However, now Depik fish are in endangered status, so it is necessary to conserve Depik fish by one way, namely domestication. To carry out domestication, information is needed about proper feed management, one of which is feeding rate. This research was conducted experimentally using a completely randomized design with 4 treatments and 3 replications. The treatments in this study included: feeding rates of 2% (A), 3% (B), 5 (C) and 7% (D). Parameters observed were absolute weight growth (PMB), absolute length growth (PPM), coefficient of diversity (KK) and water quality. The data analysis used was the F test and Duncan's test, while the water quality data were analyzed descriptively. Based on the two tests, it was found that the best feeding rate for the growth performance of Depik fish larvae was 5%. Water quality during the study was also considered normal for the life of Depik fish.